Benefits and Challenges of Zoom Tutoring during the Covid-19 Pandemic - Rempel, Cassidy; Friesen, Helen Lepp (Discourse and Writing/Rédactologie, 2022)
This study aimed to evaluate the benefits and challenges of remote/online tutoring using Zoom software/platform at a Canadian university’s Writing Centre during the Covid-19 pandemic in 2020/21. In addition to gathering data on the benefits and challenges of online tutoring, this study also provided work and research experience for a Work-Study student in the host department. The study adopted a mixed methods quantitative and qualitative approach where the employed tutors and tutees that came to the Writing Centre that term were invited to complete a survey asking them about their experience with remote/online tutoring on Zoom. The results indicated that tutors expressed a high rate of satisfaction and preference for Zoom tutoring. In contrast, tutees, although appreciative of the convenience of Zoom tutoring, demonstrated preference for an in-person face-to-face method of tutoring. Some of the benefits of Zoom tutoring for both tutors and tutees were flexibility, working from a comfortable setting like home, not having to secure childcare, and zero commute time. Some of the challenges of Zoom tutoring included technical glitches, isolation from peers and colleagues, lack of motivation, and time zone difference challenges. Besides providing valuable information for the future delivery of Writing Centre services, this study also gave the Work-Study student indispensable experience in conducting primary research. This study received ethics approval from the University Human Ethics Research Board.